Dimensional roles of justice on post-recovery overall satisfaction and behavioral intentions: Tests of casual dining experiences - Ok, Chihyung; Back, Ki-Joon; Shanklin, Carol W. (My University, 2008)
This study examined dimensional roles of justice on post-recovery overall satisfaction (OS), revisit intention (RI), and word-of-mouth intention (WOM). A 2x2x2 factorial design using experimental scenarios was used to test the proposed relationships. Responses from customers (286) and responses from undergraduate students (266) were used for data analysis. For the customer sample, interactional justice (IJ) and procedural justice (PJ) had positive effects on customer OS and WOM. Only IJ had a positive effect on RI. Distributive justice (DJ) did not have a positive effect on OS, RI, or WOM. For the student sample, IJ and DJ had positive effects on OS, RI, and WOM. However, PJ did not have a positive effect on OS, RI, or WOM. The findings indicate that service providers need to consider dimensional roles of recovery efforts not only in transactional evaluation but also in post-recovery attitudinal and behavioral outcomes. One dimension of justice, such as DJ, should not be highlighted at the cost of other dimensions in recovery efforts.
Keywords: Service recovery; Perceived justice; Post-recovery overall satisfaction; Revisit intention; Word-of-mouth intention